PENGARUH PELUMAS TERHADAP TEGANGAN ALIR DAN GAYA PENARIKAN KAWAT AISI 1006 MENGGUNAKAN METODE FEM - Destri Muliastri; Devi Eka Septyani; Prayoga Lesmana (Manutech : Jurnal Teknologi Manufaktur, 2021)
The wire drawing process is a metal forming technique. The factor affecting the final result of the draw is Lubricants. The value of the friction coefficient will have an impact on the surface quality of the wire, the use of lubricants is needed to reduce the load and surface defects of the wire. The purpose of this study was to determine the effect of lubrication on the flow stress and pulling force of AISI 1006. The lubricants used in this study have different friction coefficient values, including 0.03; 0.02 and 0.01. In this research, the method used Finite Element Method and Ansys workbench 19.0. Finite element method is done by simulating wire drawing with a die angle of 12 degrees. The results obtained will be calculated theoretically and simulated, for lubricants with different coefficient of friction have different values of flow stress and pulling force which can affect mechanical properties. The smaller the friction coefficient, the greater of the average flow stress, the percentage of theoretical calculations and simulations is 2.45%, for the effect of lubrication on the wire pulling force, the percentage is 23.25%.